2006
DOI: 10.1051/0004-6361:20065719
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the wind launching region in Herbig Ae stars: AMBER/VLTI spectroscopy of HD 104237

Abstract: Aims. We investigate the origin of the Brγ emission of the Herbig Ae star HD 104237 on Astronomical Unit (AU) scales. Methods. Using AMBER/VLTI at a spectral resolution R = 1500 we spatially resolve the emission in both the Brγ line and the adjacent continuum. Results. The visibility does not vary between the continuum and the Brγ line, even though the line is strongly detected in the spectrum, with a peak intensity 35% above the continuum. This demonstrates that the line and continuum emission have similar si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
51
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 20 publications
(40 reference statements)
9
51
1
Order By: Relevance
“…AMBER/VLTI observations show that most of the K band continuum flux arises from a ring of radius R = 0.5 au (Tatulli et al 2007), in agreement with the location of the dust sublimation radius in the circumbinary disc (Garcia et al 2013). …”
Section: Introductionsupporting
confidence: 63%
“…AMBER/VLTI observations show that most of the K band continuum flux arises from a ring of radius R = 0.5 au (Tatulli et al 2007), in agreement with the location of the dust sublimation radius in the circumbinary disc (Garcia et al 2013). …”
Section: Introductionsupporting
confidence: 63%
“…. Martin-Zaïdi et al (2008) found excited and hot H 2 gas from far-UV spectra, while Tatulli et al (2007) explain the origin of the Brγ emission by an inner disk wind, originating at about 0.5 AU from the star.…”
Section: Stars With Measurements Suggestivementioning
confidence: 95%
“…For many of our targets with a detected magnetic field, reports on the detection of excited, hot inner disk gas exist, which may be attributed to a gaseous accretion ring close to the star (see especially Tatulli et al 2007;Isella et al 2008).…”
Section: Hot Disk Gasmentioning
confidence: 99%
“…Interferometric observations of the Brγ line show that the emission originates in a region more compact than the continuum, but more extended than the magnetosphere; its most likely origin is a stellar or disk wind (Kraus et al 2008). Other sources exhibit similar signatures in Brγ, attributed to an equatorial atomic disk wind within a few au of the star (Malbet et al 2007;Tatulli et al 2007;Eisner et al 2010;Benisty et al 2010b;Weigelt et al 2011).…”
Section: Kinematic Structure and Size Of The Launch Regionmentioning
confidence: 97%